Advanced functional materials a perspective from theory and experiment - Sanyal, Biplab; Eriksson, Olle (Science and technology of atomic, molecular, condensed matter & biological systems, 2012)
This book deals with functional materials that are in the frontiers of current materials science and technology research, development and manufacture. The first of its kind, it deals with three classes of materials, (1) magnetic semiconductors, (2) multiferroics, and (3) graphene. Because of the wide popularity of these materials there is a strong need for a book about these materials for graduate students, new researchers in science and technology, as well as experienced scientists and technologists, technology based companies and government institutes for science and technology. The book will provide this broad audience with both theoretical and experimental understanding to help in technological advances in the development of devices and related new technologies based on these very interesting and novel materials.